Environmental Education as Part of Pancasila Moral Education - Yuwantika, Unfika (Journal of Creativity Student, 2018)
Pancasila Education is a compulsory and important subject to be embedded in the education system in Indonesia, for all groups such as for students and campuses in universities. Pancasila education itself has a useful role as a reinforcement that we can cultivate and we can describe in our daily lives. The role of the Pancasila is very influential because with the Pancasila there will be the formation of moral education, character education, ethics and etiquette. Which is used in the family environment, school environment, community environment and so forth. But in fact the basics of the Pancasila are only skewed as guidelines or only as writing Not many know what the true meaning is so that there are still many or some people not all hold firm and arbitrary, even not so caring, therefore we as the millennial generation of the nation must care more about the importance of the Pancasila as an example that we can take in the Pancasila regarding the preservation of the environment itself, that is, we must love the homeland, we must love nature, we must preserve and protect the environment and everything, do not damage the natural ecosystem, do not abuse what has been provided by nature. So that we have to be balanced with nature, what we mean when nature gives us what we need then we must be able to give what nature needs, namely by preservation. It is also related to the Pancasila values that we must practice and apply